Comparative effectiveness and tolerance of immunosuppressive treatments for idiopathic membranous nephropathy: A network meta-analysis. - Song Ren; Ying Wang; Ying Wang; Li Xian; Tadashi Toyama; Meg Jardine; Guisen Li; Vlado Perkovic; Daqing Hong (PLoS ONE, 2017)
Background Immunosuppressive agents in general are shown to prevent renal progression and all-cause mortality in idiopathic membranous nephropathy (IMN) patients with nephrotic syndrome. However, the efficacy and safety of different immunosuppressive treatments have not been systematic assessed and compared. A network meta-analysis was performed to compare different immunosuppressive treatment in IMN. Methods Cochrane library, MEDLINE, EMBASE and trial register system were searched for randomized controlled trials reporting the treatments for IMN to May 3, 2016. Composite endpoint of mortality or end-stage kidney disease (ESKD), complete or partial proteinuria remission and withdrawal because of treatment adverse events were compared combing direct and indirect comparison using network meta-analysis. Ranking different immunosuppressive treatments in the outcomes were analyzed by using surface under the cumulative ranking curve (SUCRA). Results Total 36 randomized controlled trials (n = 2018) covering 11 kinds of treatments were included. Compared with non-immunosuppressive treatment, only cyclophosphamide (CTX) and chlorambucil significantly reduced the risk of composite outcome of mortality or ESKD while combining the direct and indirect comparison (OR = 0.31, 95%CI: 0.12-0.81 and OR = 0.33, 95%CI: 0.12-0.92). CTX increased the composite outcome of complete remission (CR) or partial remission (PR) (OR = 4.29, 95%CI: 2.30-8.00) but chlorambucil did not (OR = 1.58, 95%CI: 0.80-3.12) as compared with non-immunosuppressive treatment. Chlorambucil also significantly increased the withdrawal risk (OR = 3.34, 95%CI: 1.37-8.17) as compared to CTX. Both tacrolimus (OR = 3.10, 95%CI: 1.36-7.09) and cyclosporine (CsA) (OR = 2.81, 95%CI: 1.08-7.32) also significantly increased the rate of CR or PR as compared with non-immunosuppressive treatment (without significant difference as compared with CTX), while ranking results showed that cyclosporine or tacrolimus was with less possibility of drug withdrawal as compared to CTX. Conclusions Cyclophosphamide and chlorambucil reduce risk of ESKD or death in IMN with nephrotic range proteinuria, but carry substantial toxicity that may be lower for cyclophosphamide. Tacrolimus and cyclosporine increase the possibility of proteinuria remission with less drug withdrawal, but the effects on kidney failure remain uncertain.